Perbandingan Aktivitas ekstrak Jahe Merah (Zingiber officinale var. rubrum) dan Kunyit (Curcuma longa L) Terhadap Respon Imun Pada Hewan Uji: Tinjauan Literatur - Gita Novianti Lismawan; Dia Septiani; Biandra Cinta Ramadhani; Arifa Salsabilla Ramadhany (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The immune system plays a crucial role in protecting the body against various pathogenic agents; therefore, efforts to enhance immune function through natural approaches are essential. This study aims to systematically compare the immunomodulatory effects of red ginger (Zingiber officinale var. rubrum) and turmeric (Curcuma longa L.) based on a systematic literature review of preclinical experimental studies. Literature was systematically collected from two electronic databases, PubMed and Google Scholar, covering publications from 2010 to 2025, using keywords related to Zingiber officinale var. rubrum, “red ginger”, Curcuma longa, “turmeric”, “immune”, “immunity”, “cytokine”, “immune response”, and “immunomodulatory effect”. Of the 260 articles identified, only 10 studies met the inclusion criteria and were analyzed further. Based on reported immunological response patterns, red ginger predominantly influences innate immune parameters measurable during the early phase of immune activation, including increased macrophage phagocytic activity, enhanced production of proinflammatory cytokines (IL-1β and IFN-γ), and activation of natural killer (NK) cells. In contrast, turmeric demonstrates significant effects on adaptive immune parameters that are generally evaluated over longer intervention periods, mediated by curcumin through inhibition of the NF-κB signaling pathway, upregulation of anti-inflammatory cytokines (IL-10), and enhancement of regulatory T cell (Treg) function to maintain immunological homeostasis. Both red ginger and turmeric exhibit potential as natural immunomodulatory agents that support immune defense; however, their mechanisms and magnitude of effects differ. Red ginger tends to elicit more rapid immune responses, whereas turmeric exerts more sustained regulatory effects. In conclusion, the utilization of red ginger and turmeric may serve as preventive and therapeutic phytotherapeutic alternatives to enhance immune function. Nevertheless, as the available evidence is largely derived from animal experimental studies, further well-designed pharmacokinetic studies and controlled clinical trials are required to confirm efficacy, safety, and optimal formulations in humans.